A valuable option: Clinical and radiological outcomes of braided suture tape system augmentation for spring ligament repair in flexible flatfoot. (December 2020) - Tang, Chris Yuk Kwan; Ng, Ka Ho
Highlights: InternalBrace augmentation of spring ligament repair showed excellent clinical and radiographic outcomes. Comparing to the usual hindfoot reconstruction procedures, InternalBrace created more number of patients with single leg stance and better correction of forefoot abduction. It is a reasonable alternative option in hindfoot reconstruction. In addition, it showed superior corrective power with similar operation time, but avoiding the complications from bony procedures. Abstract: Background: The purpose of this study was to evaluate the clinical and radiological outcomes of the briaded suture tape system augmentation in the treatment of flexible flatfoot. Methods: Patients who underwent suture tape system augmentation in addition to spring ligament repair and flexor digitorum longus (FDL) transfer were reviewed. Clinical and radiological outcomes were studied. The results were compared to a matched control group who underwent the conventional surgical treatment, which involved FDL transfer only or FDL transfer plus medial sliding calcaneal osteotomy. Results: A total of 40 patients (11 males and 29 females) who underwent hindfoot reconstruction for flexible flatfoot (Johnson stage 2) were reviewed. There were 18 patients in the suture tape system group and 22 patients in the control group. In the suture tape system group, there was excellent improvement in patients' symptoms, AOFAS score (97.9 improved from 76.7) and significantly more number of patients with stable single leg stance. Radiographic parameters improved postoperatively too. Conclusions: This is the first clinical study which studied the outcome of suture tape system augmentation for spring ligament repair. Patients with suture tape system reconstruction showed more number of patients with single leg stance and better correction of forefoot abduction. It is a reasonable component of hindfoot reconstruction.